The Pacific right to know in the Digital Age - Francis Herman (Asia Pacific Network, 2010)
Commentary: The explosion of mobile telephony in some islands of the South Pacific has literally connected our peoples to the rest of the world and opened up access to a wide variety of information. While there are some who view this expansion as a huge threat to the traditional media, the ongoing development and expansion of this technology presents the traditional media with enormous opportunities to reach a wider audience at basically little cost. But of course there is also a financial cost to the consumer, which in the case of the South Pacific can be a significant issue.